The role of management accounting in competition policy: The case of the inverness route - Tengku Abdullah, Tengku Akbar (Universiti Utara Malaysia, 2001)
Although competition policy is an important area for accounting research, contributions from management accountants are lacking. This article aims to show that management accountants can help clarify number of issues in competition policy using diagnostic tools such as analytical constructs and concepts of cost to establish relevant facts and cost. Accordingly, this article demonstrates that the employment of such diagnostic tools can give insights into anti-competitive behavioral issues in competition policy, as illustrated in the Inverness route case.